Gambaran Koping Spiritual Remaja Pengguna Napza Di LPKA Kelas I Tangerang Dan Blitar - Pieter Pindardhi; Jacquelinda Sandra Sembel; Maria Susila Sumartiningsih; Sumiaty Aiba (Malahayati Nursing Journal, 2022)
ABSTRACT Indonesian Child Protection Commission recorded that the number of teenagers involved in drug abuse shot up to almost 400% from 2011 – 2014. These teenagers have great need for spiritual coping mechanism to face challenges in life. As they are serving their terms in detention, lose the opportunity to get education from their parents to develop their spiritual coping ability. This research is aimed to get the descriptions of spiritual coping mechanism of teens involved in drug abuse in Lembaga Pembinaan Khusus Anak or LPKA (Special Institution/Center for Child Rehabilitation). The research was conducted using convenience sampling and descriptive qualitative methods. The teenagers involved in drug abuse in LPKA I Tangerang and Blitar with the following inclusion criteria: using drug, serving a minimal of 1 year in the detention center, aged between 13 to 17 years old, Christian, and living with their family before admitted to the center, was an active student of a school when captured by the police, able to communicate in Bahasa Indonesia, and willing to take part in the research. Data collection was done using in-depth interview. The data from the interviews were analyzed and categorized based on main reason the using drugs, teenager outlook to coping sprituality and relationship trust embraced, sources of spiritual coping support and how to use. Teenagers use drugs when problem ecounter as escape reason to clear the problem, while the observation sprituality coping believe that God can help solve the problem. However, it is not appropriate to choose spirituality coping and not to use it effectively as a source of support. Furthermore, they are committed to making spiritual changes after serving their sentence. Spiritual coping in supporting the recovery of drug users is very important. The quantitative and qualitative research covers teenager of various religions in terms of spiritual care and more counseling during adolescence in LPKA. Keywords: Teenager, Drugs, Spiritual Coping ABSTRAK Komisi perlindungan anak Indonesia mencatat jumlah remaja pengguna NAPZA meningkat hampir 400% selama 2011-2014. Hal ini berakibat semakin banyak anak menjalani sanksi hukuman di Lembaga Pembinaan Khusus Anak (LPKA). Mereka kehilangan bimbingan orangtua untuk mengembangkan kemampuan koping spiritualnya. Penelitian ini bertujuan mendapatkan gambaran koping spiritual remaja pengguna NAPZA di LPKA. Penelitian ini menggunakan metode deskriptif kualitatif. Sampel dipilih dengan convenience sampling, mencakup remaja pengguna NAPZA di LPKA Kelas 1 Tangerang dan Blitar. Kriteria inklusinya: pengguna NAPZA yang menjalani masa tahanan minimal 1 tahun, berumur 13-17 tahun, beragama Kristiani, sebelum menjalani masa tahanan tinggal bersama keluarga, berstatus sebagai siswa pada suatu sekolah saat ditangkap, mampu berbahasa Indonesia, dan bersedia ikut serta dalam penelitian. Pengumpulan data dilakukan secara in depth interview. Data hasil wawancara dianalisa dan dikelompokkan berdasarkan alasan utama menggunakan NAPZA, pandangan remaja terhadap koping spiritualitas dan hubungan kepercayaan dianut, sumber koping sebagai dukungan rohani dan cara menggunakan. Para remaja menggunakan NAPZA saat menghadapi masalah sebagai alasan pelarian menyelesaikan masalah, sedangkan tinjauan pandangan koping spiritual yakin Tuhan dapat menolong menyelasiakan masalah.  Namun, tidak tepat memilih koping spiritualitas dan tidak mendayagunakannya secara efektif sumber dukungan. Selanjutnya mereka berkomitmen untuk melakukan perubahan rohani setelah selesai menjalani masa hukumannya. Koping spritual dalam mendukung pemulihan remaja pengguna NAPZA sangat penting. Perlu adanya penelitian kuantitatif dan kualitatif mencakup remaja beragam agama ditinjau dari siraman rohani dan konseling lebih banyak selama remaja di LPKA. Kata kunci: Remaja, NAPZA, Coping Spritual